Main lines of research in the field of higher education in Peru: Towards Concerted Prioritization - Huayanay-Espinioza, Carlos A. (2019)
As part of the efforts to prioritize lines of research in the field of higher education in Peru, the project Improvement of Higher Education Quality (PROCALIDAD) convened management specialists and members of academia to create working groups. After the presentation of a characterization of the general problem in this field, a debate was started, and this concluded in the preparation of a joint proposal for a research agenda, which prioritized certain lines such as (a) the need for articulation between basic and higher education for a generation of competencies in the applicants; (b) the need to emphasize the teaching professional career aimed at improving the quality of educational institutions; (c) the need to seek alternative financing mechanisms involving the private sector; (d) the need for greater clarity in existing regulations and standards, and (e) the need to foster the connection between higher education, business, and State, in order to achieve a higher level of competitiveness and development. These guidelines will allow to expand the discussion and generate a series of public policies conducive to strengthening research in higher education institutions and promoting more relevant research for the country in the medium and long term.